Empowerment of rural young people in informal farm entrepreneurship: The role of corporate social responsibility in Nigeria's oil producing communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2021)
Purpose - The purpose of this paper is to critically examine the corporate social responsibility initiatives of multinational oil companies in Nigeria. Its main focus is to investigate the impact of the global memorandum of understanding (GMoU) on equipping the rural young people with essential farming skills and knowledge for adoption and application of modern agricultural inputs in the Niger Delta region. Design/methodology/approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially crosssectional, describing and interpreting the current situation. A total of 800 rural young people were sampled across the oil producing region. Findings - The results from the use of combined propensity score matching and logit model indicate that the GMoU model has a significant impact on development of informal farm entrepreneurship generally, but somewhat undermined rural young people in the targeted agricultural clusters. Practical implications - This suggests that youth-specific CSR farm projects can be effective in providing young people with the extra push needed to tackle the knowledge gap and poor agronomic that erect the below-per yield and lack of competitiveness of small-holder farmers in the region. Social implications - It implies that a coherent and integrated CSR response from business would be necessary to unlock investment opportunities on young people in farms for agricultural competitiveness and food security in Africa. Originality/value - This research adds to the literature on informal farm entrepreneurship and rural communities' debate in sub-Saharan Africa. It concludes that business has obligation to help in solving problems of youth unemployment in developing countries.
Keywords: 330; Global memorandum of understanding (GMoU); Rural young people; Informal farm entrepreneurship; sub-Saharan Africa